Fragment-Based Whole Cell Screen Delivers Hits against M. tuberculosis and Non-tuberculous Mycobacteria - Moreira, Wilfried; Lim, Jia Jie; Yeo, Si Ying; Ramanujulu, Pondy M.; Dymock, Brian W.; Dick, Thomas (Frontiers in Microbiology, 2016)
Reactive multi-target ‘fragment drugs’ represent critical components of current tuberculosis regimens. These compounds, such as pyrazinamide, are old synthetic antimycobacterials that are activated inside Mycobacterium tuberculosis bacilli and are smaller than the usual drug-like, single-target molecules. Based on the success of small ‘dirty’ drugs in the chemotherapy of tuberculosis, we suggested previously that fragment-based whole cell screens should be introduced in our current antimycobacterial drug discovery efforts. Here, we carried out such a screen and characterized bactericidal activity, selectivity and spectrum of hits we obtained. A library of 1725 fragments was tested at a single concentration for growth inhibitory activity against M. bovis BCG as screening strain and 38 of 116 primary hits were confirmed in dose response analyses to be active against virulent M. tuberculosis. Bacterial kill experiments showed that most hits displayed bactericidal activity at their minimal inhibitory concentration. Cytotoxicity assays established that a large proportion of hits displayed a favorable selectivity index for mammalian cells. Importantly, one third of M. tuberculosis active fragments were also active against M. abscessus and M. avium, two emerging non-tuberculous mycobacterial pathogens, opening the opportunity to develop broad spectrum antimycobacterials. Activity determination against Gram positive (Staphylococcus aureus) and Gram negative (Escherichia coli, Klebsiella pneumonia, Acinetobacter baumanii, Pseudomonas aeruginosa) bacteria, as well as fungi (Candida albicans, Cryptococcus neoformans) showed only a small overlap indicating a generally narrow spectrum of these novel antimicrobial hits for mycobacteria. In conclusion, we carried out the first fragment-based whole cell screen against bacteria and identified a substantial number of hits with excellent physicochemical properties and dual activity against M. tuberculosis and non-tuberculous mycobacterial pathogens. These hits will now be evaluated in animal models of mycobacterial infection to determine whether any of them can be moved forward as a new antimycobacterial fragment drug candidate.